Metal Ion Emission and Corrosion Resistance of 3D-Printed Dental Alloy - Tomova, Zlatina; Vlahova, Angelina; Stoeva, Iliyana; Zhekov, Yanko; Vasileva, Elena (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Prosthetic rehabilitation requires application of materials with different chemical, mechanical and biological properties which must provide longevity, esthetics, and safe use. Corrosion resistance and metal ion emission are the major factors defining biocompatibility of base dental alloys. Digitalization in Dentistry leads to development of new materials suitable for CAD/CAM technologies. Cobalt-chromium powder alloys are used for additive manufacturing of PFM crowns. The aim of this study is to evaluate corrosion resistance and metal ion emission of Cobalt-chromium dental alloy for 3D printing. Materials and methods: 35 metal copings were designed using digital files of intraoral scans of 35 patients. CoCr dental alloy EOS CobaltChrome SP2 (EOS, Germany) was used to produce the copings by DMLS (direct laser metal sintering). Tests for presence of free Cobalt ions were conducted at several stages of the production process. Open circuit potential measurements were conducted 2 hours, 24 hours, and 7 days after placing the copings in artificial saliva. Metal ion emission was assessed by inductively coupled plasma mass spectrometry (ICP–MS) after 24 hour- and 7 day-period of stay in the solution. Results: Tests for free Cobalt ions were positive at all stages during production of the metal copings. Eocp measurements showed high corrosion resistance which increased in time. ICP-MS showed significantly higher amount of cobalt and chromium ions after 7-day period of stay compared to 24-hour period. Conclusion: Studied alloy showed high corrosion resistance at in vitro conditions. Detected ion emission requires further investigations on the biological properties.